THE EMERGENCE OF SMES IN COSTA RICA FROM AN HISTORICAL-ECONOMIC PERSPECTIVE (1950-2018) - Cousin Brenes, Kathia (2021)
This paper analyzes the emergence of smes in Costa Rica from an economic-historical perspective, during the years of 1950-2018. This periodization corresponds to the political structure of each period, according to the business development and the context to be studied during the import substitution development models (1948-1979) and the economic liberation (1982-2018). From the study, it is highlighted that, although at the end of the 20th century and the beginning of the 21st century the number of smes increases, they face greater business challenges, because the State’s economic policy is more inclined to globalized markets, aspects in which the previous enterprises do not have competitive advantages.